(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article shows that such great geniuses in the field of science have been educated in educating our youth, that their great achievements in the development of science still retain their value, that our unique and unique scientific and spiritual heritage is a source of strength and inspiration. is becoming a source.